Contribution of psychological variables in the perception of pain in individuals with orofacial pain - Bonafé, Fernanda Salloume Sampaio; Marôco, João; Campos, Juliana Alvares Duarte Bonini (Headache Medicine, 2017)
Comunicação Curta